Cassava and maize intercropping system - The effect of varieties and and plant populations - Ezumah, H.C.; Lawson, T.L. (1990)
Maize dominated cassava irrespective of cassava or maize growth habit and the optimum maize population giving the highest production based on relative yield total or land equivalent ratio varied with maize variety in a tropical Alfisol at Ibadan, transition humid/subhumid zone in West Africa. The sparsely vegetative, early maize supported higher intercrop maize population (up to 80,000 ha−1) than the late maturing, highly vegetative TZSRW. Because there is a compensatory relationship in the yields of the two crop components, the choice of an appropriate crop type and maize population in cassava + maize intercrop system will depend on the relative economic importance of each crop component.